Thiopyrimidine derivatives as new and effective corrosion inhibitors for mild steel in hydrochloric acid: Electrochemical and quantum chemical studies - Singh P.; Singh A.; Quraishi M.A. (My University, 2025)
The corrosion inhibition properties of thiopyrimidines derivatives viz. 5-cyano-6-phenyl-2-thioxo-2,3-dihydropyrimidin-4-one (TP-1), 5-cyano-2-thioxo-6-(p-tolyl)-2,3 dihydropyrimidin-4-one (TP-2), 5-cyano-6-(4-methoxyphenyl)-2-thioxo-2,3-dihydropyrimidin-4-one (TP-3), 6-(4-(dimethylamino)phenyl)-5-cyano-2-thioxo-2,3-dihydropyrimidin-4-one (TP-4) were investigated as corrosion inhibitors by weight loss, electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization methods. Among all thiopyrimidines TP-4 exhibited maximum efficiency of 97% at 200 mg L-1. The results of electrochemical studies revealed that all four TPs were adsorbed on the metal surface by adsorption mechanism and behave as mixed type inhibitors with predominant control on cathodic reaction. The SEM-EDS/AFM/XPS methods were used to corroborate the mechanism of inhibition. © 2015 Taiwan Institute of Chemical Engineers.